2015
DOI: 10.4162/nrp.2015.9.4.404
|View full text |Cite
|
Sign up to set email alerts
|

Is the association of continuous metabolic syndrome risk score with body mass index independent of physical activity? The CASPIAN-III study

Abstract: BACKGROUND/OBJECTIVESAlthough the association of body mass index (BMI) with metabolic syndrome (MetS) is well documented, there is little knowledge on the independent and joint associations of BMI and physical activity with MetS risk based on a continuous scoring system. This study was designed to explore the effect of physical activity on interactions between excess body weight and continuous metabolic syndrome (cMetS) in a nationwide survey of Iranian children and adolescents.SUBJECTS/METHODSData on 5,625 sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…This cluster of risk factors is a better predictor of cardiovascular health than is any of the components individually [ 11 , 12 ]. Since the prevalence of MetS is lower in children and adolescents than in adults, many epidemiologic studies have used a continuous value of the MetS risk score (cMetS) instead of a binary distinction between MetS and potential risk factors [ 13 , 14 , 15 ]. The cMetS is more sensitive and less error-prone than a dichotomous approach [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This cluster of risk factors is a better predictor of cardiovascular health than is any of the components individually [ 11 , 12 ]. Since the prevalence of MetS is lower in children and adolescents than in adults, many epidemiologic studies have used a continuous value of the MetS risk score (cMetS) instead of a binary distinction between MetS and potential risk factors [ 13 , 14 , 15 ]. The cMetS is more sensitive and less error-prone than a dichotomous approach [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cMetS is more sensitive and less error-prone than a dichotomous approach [ 16 ]. Cardio-metabolic risk is a progressive function of other risk factors such as MetS components [ 15 ], and so this study used a continuous assessment to detect changes in cardio-metabolic risk.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, this is the largest study showing that unfavorable body composition parameters (obesity, visceral adiposity, and sarcopenia) additively increase the risk for MS. Previous studies have shown that visceral adiposity [ 7 11 ], sarcopenia [ 30 32 ], and obesity [ 20 23 ] were associated with an increased risk for MS. However, most of these studies analyzed the association of only a single body composition parameter with MS; studies analyzing the association between multiple body composition parameters and MS have been rare [ 43 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The z-score was the earliest statistical technique used to generate a cMetS score by Batey et al [34] in 1997. The cMetS is computed using the z-score by taking the difference between the sample mean of each attribute and each sample value in the population, and dividing the result by the standard deviation of each attribute in the population [35], [36], [38], [43], [45]. The PCA operates by decreasing the dimensionality of the attributes of a dataset in order to make data more interpretable while preserving the relevant information [47].…”
Section: A Statistical Techniquesmentioning
confidence: 99%